TPH and suicidal behavior: a study in suicide completers - Turecki, G; Zhu, Z; Tzenova, J; Lesage, A; Séguin, M; Tousignant, M; Chawky, N; Vanier, C; Lipp, O; Alda, M; Joober, R; Benkelfat, C; et al. (Molecular psychiatry, 2001)
An association between the gene that codes for tryptophan hydroxylase (TPH)-the rate-limiting enzyme in the synthesis of serotonin-and suicidal behavior has been investigated with some detail in samples of living subjects who attempted suicide. In this study, we investigated TPH and suicide completion, the most severe form of suicidal behavior. A relatively large sample of suicide completers (n = 101) was genotyped at three TPH loci (two polymorphisms in the promoter region, A-6526G and G-5806T, and one in intron 7, A218C) and compared to psychiatrically normal living controls (n = 129). Although no significant differences were found between groups for genetic variation at single loci, haplotype analysis revealed that one haplotype (-6526G -5806T 218C) was significantly more frequent among suicide cases than in normal controls (chi(2) = 11.30, df = 2, P = 0.0008; OR = 2.0 CI: 1.30-3.6). Further analyses suggested that this haplotype is particularly more frequent among subjects who committed suicide using violent methods. Similar results were observed in recent haplotype analyses in suicide attempters, which found that the equivalent of haplotype -6526G -5806T 218C was more frequent in impulsive attempters (Rotondo et al, Mol Psychiatry 1999; 4: 360-368). Our results replicate in suicide completers previous data observed in suicide attempters. These and other results continue to point to the substantial role that the gene that codes for TPH may play in the neurobiology of suicidal behavior.